2022
DOI: 10.1039/d1sm01808f
|View full text |Cite
|
Sign up to set email alerts
|

Formation and growth of lithium phosphate chemical gardens

Abstract: We show that a chemical garden can be developed from an alkaline metal precipitate using a flow-driven setup. By injecting sodium phosphate solution into lithium chloride solution from below, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Contemporary research has identified several other growth regimes, 3,4 quantified the underlying dynamics, 5 and greatly expanded the range of product materials to include insoluble metal sulfides, 6 carbonates, 7 phosphates 8,9 as well as polyoxometalates, 10,11 and even hydrogels. 12 Furthermore, technical applications are being explored as inexpensive absorbent/catalytic materials to fight chemical spills, 13 sensor-platforms for microfluidics, 14 and biomimetic scaffolds for the growth of osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary research has identified several other growth regimes, 3,4 quantified the underlying dynamics, 5 and greatly expanded the range of product materials to include insoluble metal sulfides, 6 carbonates, 7 phosphates 8,9 as well as polyoxometalates, 10,11 and even hydrogels. 12 Furthermore, technical applications are being explored as inexpensive absorbent/catalytic materials to fight chemical spills, 13 sensor-platforms for microfluidics, 14 and biomimetic scaffolds for the growth of osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Flow-injection systems provide a convenient control of the various growth types and dynamical activities. [8][9][10][11][12][13] Most of the underlying self-assembled architectures have been explored by utilizing a wide range of inorganic materials, including even alkali 14 or light-sensitive metal ions. 15 However, the self-organization of pure organic garden architectures is not much explored; it is limited to a few investigations, e.g., formation of iron(III) oleate in organic solvents, 16 instabilities of tubular chitosan hydrogels, 17,18 and alginate coiling.…”
Section: Introductionmentioning
confidence: 99%
“…The breadth of chemical garden materials is extremely diverse, including metal (hydr)­oxides, sulfides, carbonates, borates, and phosphates as well as polyoxometalates and organic polymers. , Moreover, some of these precipitates are major constituents of the chimney-like structures in hydrothermal vent fields and have been implicated in the origins-of-life as a result of their porous and catalytic nature. Possible naturally occurring chemical gardens have also been discussed as potential sources for the misidentification of Earth’s earliest microfossils , and could, in a similar fashion, complicate the search for remnants of life on Mars and moons with water–rock interfaces, such as Europa and Enceladus .…”
Section: Introductionmentioning
confidence: 99%